Assessing the effect of oral activated vitamin D on overall survival in hemodialysis patients: a landmark analysis - Jo-Yen Chao; Hsu-Chih Chien; Te-Hui Kuo; Yu-Tzu Chang; Chung-Yi Li; Ming-Cheng Wang; Yea-Huei Kao Yang (BMC Nephrology, 2018)
Abstract Background Patients with end stage renal disease have a high all-cause and cardiovascular mortality. Secondary hyperparathyroidism and vitamin D deficiency are considered part of the mechanism for the excess mortality observed. We aimed to evaluate the relationship between vitamin D use and all-cause mortality. Methods In this retrospective cohort study, we included all incident patients who started hemodialysis in Taiwan between 2001 and 2009. Patients were followed from landmark time, i.e., the 360th day from hemodialysis initiation, through the end of 2010 or death. We evaluated the association between activated vitamin D use or not before landmark time and all-cause mortality using conditional landmark analysis with Cox regression. We used group-based trajectory model to categorize high-dose versus average-dose users to evaluate dose-response relationships. Results During the median follow-up of 1019 days from landmark time, vitamin D users had a lower crude mortality rate than non-users (8.98 versus 12.93 per 100 person-years). Compared with non-users, vitamin D users was associated with a lower risk of death in multivariate Cox model (HR 0.91 [95% CI, 0.87–0.95]) and after propensity score matching (HR 0.94 [95% CI, 0.90–0.98]). High-dose vitamin D users had a lower risk of death than conventional-dose users, HR 0.75 [95% CI, 0.63–0.89]. The association of vitamin D treatment with reduced mortality did not alter when we re-defined landmark time as the 180th day or repeated analyses in patients who underwent hemodialysis in the hospital setting. Conclusions Our findings supported the survival benefits of activated vitamin D among incident hemodialysis patients.